Wind forecast employing the WRF model for a wind potential analysis - Ghizoni, Mariana Medeiros (2019)
The WRF (Weather Research and Forecast) is a numerical modeling applied to the atmosphere. This model was developed for weather forecasting and investigation of atmospheric mesoscale phenomena. The WRF is a public domain and free distribution, with different applications ranging from the field of meteorology to engineering, and can be applied in situations of idealized atmosphere or real atmosphere. Presently, the wind field simulated by this model has been used as real data. Thus, the WRF model started to be employed in wind analysis for wind power generation. In this work, the wind field was simulated using the WRF model, in Cachoeira do Sul, Rio Grande do Sul, Brazil.